The Role of Social Networks Sites in Prioritizing Political Reform among University Professors - التميمي, خلف كريم; محمد, حسين سعدي (ALBAHITH ALALAMI, 2015)
With the development of modern mass media and the prevalence of use continues to both researchers and practitioners their efforts to understand how the media affect Hzha on both the individual and the institutions, society and culture as a whole, which means that the need to develop models and theories explain and predict the effects of the use of such means, therefore, the study of modern technologies of communication and information as an area of ​​research has become mature to establish the intellectual base cohesive, but they are not mature enough, which calls for more research developments therefore become social networking sites online, (Facebook, and YouTube, and straining) known today as the new social media, which is witnessing the dynamics of development and deployment movement, it has been in its infancy virtual community on a small and limited scale, and then he grew with time to shift from information tool text written to the audio-visual media tool influence the decisions of those affected and their responses, under pressure from influential force used in the impact of personal styles of the individual (auditory, visual, and sensory ), that social networking sites have contributed to the activation of the principle of participation to achieve the desire of each category in the interests and activities itself, it also has a role in networking and advocacy and lobbying and interaction and influence with leaders of non-organization, and the achievement of social responsibility if properly invested and exploited and directed well, it has has been able to transform words and ideas and trends to ready work projects for implementation is social networking sites via the Internet ", from the latest communications technology products and the most popular, despite the fact that these sites were established in the foundation of social communication between individuals, their use extended to include political activity during the trading information political events, as well as the invitation to attend seminars or demonstrations.